Mechanical Amorphization and Recrystallization of Mn-Co(Fe)-Ge(Si) Compositions - Antonio Vidal-Crespo (Metals, 2019)
Mechanical alloying using a planetary ball mill allowed us to obtain two homogeneous systems formed by units with nanometer size and MnCo0.8Fe0.2Ge1−xSix stoichiometry (x = 0 and 0.5). The phase evolution of the systems with the milling time was analyzed using X-ray diffraction. Thermal stability of the final products was studied using differential scanning calorimetry. Room temperature 57Fe Mössbauer spectroscopy was used to follow the changes in the Fe environments. A paramagnetic Co-based amorphous phase developed in both alloys as milling progressed. However, while the presence of Si stabilized the Mn-type phase, mechanical recrystallization was observed in a Si-free composition leading to the formation of a MnCo(Fe)Ge intermetallic (Pnma space group) with a crystal size of 7 ± 1 nm. Mössbauer results indicate that Fe atoms migrate from the initial bcc phase to the amorphous and intermetallic phases.